Transgression of the romantic movement in Western society: The unity of Romanticism and Modernism - A. E. Kapishin (RUDN journal of Sociology)
The article is the first and the most general part of the study and focuses on the thesis that has been put forward before but is not entirely clear and widespread in the Russian science: in Western cultures and societies in the 19th-20th centuries, a single “romantic movement” developed and unfolded in several stages. This romantic trend is considered not from the perspective of art history but in a broader sense - as a trend that determines the culture of Western society. Romanticism (“high romanticism”) is the first representative of this movement; all its “generic features” are manifested in it, considered as principles not only of art but also of a worldview - unfolding in philosophy and determining the parameters of culture. “High Romanticism” is followed by Modernism, in which decadence (“late Romanticism”, Modernism of the late 19th century) is distinguished from Modernism of the 20th century, often called avant-garde in the broader sense (not only a movement in painting and art but also a new worldview). Romanticism, decadence and the avant-garde are not simply social-cultural phenomena that follow one another in time, are different in some ways and similar in others, but also are stages in the development of a single system of principles of spiritual culture (according to T. Mann, stages of a single “intellectual movement”). The study is also based on the idea that Romanticism is an antagonist of the movement that does not have a single name but has a quite clear meaning: sometimes, using the terminology of art to define the entire “intellectual movement”, it is called “realistic”, or, using the terminology of science, it is called “positivist” (and associated with the “principles of the Enlightenment”). Two “directions of thought” make up a pair, their struggle determines social-cultural dynamics; therefore, we can speak of their dualism. Thus, F. Nietzsche asserted the dualism of the Apollonian and Dionysian principles, although without reducing the Apollonian principle to the “Enlightenment” that limited the capabilities of the intellect. The common issue of all articles in the study is the transgression of the romantic trend in Western society from the 19th to the first half of the 20th century. The term “transgression” can be replaced by “advance” or “spread”, since the author’s idea is that the romantic movement not only coexisted with the realistic one, changing one’s forms, but gradually and irreversibly displaced it in Western societies to eventually become the dominant of their culture. In the early 19th century, during the time of “high romanticism,” the cultural dominant of Western society was the “Enlightenment” trend expressed in classicist art and positivist science; by the end of the era of “high romanticism”, in the mid-20th century, the dominant changed and led to the development of postmodernism which also belongs to the romantic movement.